2018
DOI: 10.7554/elife.33092
|View full text |Cite
|
Sign up to set email alerts
|

Rem2 stabilizes intrinsic excitability and spontaneous firing in visual circuits

Abstract: Sensory experience plays an important role in shaping neural circuitry by affecting the synaptic connectivity and intrinsic properties of individual neurons. Identifying the molecular players responsible for converting external stimuli into altered neuronal output remains a crucial step in understanding experience-dependent plasticity and circuit function. Here, we investigate the role of the activity-regulated, non-canonical Ras-like GTPase Rem2 in visual circuit plasticity. We demonstrate that Rem2-/- mice f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 101 publications
(162 reference statements)
2
20
0
Order By: Relevance
“…Likewise, loss of such inhibition leading to increased CaMKII catalytic activity, such as by Rem2 deletion, could lead to widespread changes in cellular structure and function. This is consistent with the many alterations we observe in our past and current studies of Rem2 deletion [51, 54, 55, 67, 7679]. Compellingly, the ability for Rem2 to inhibit CaMKII catalytic activity has already been linked to regulation of dendritic complexity [79].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Likewise, loss of such inhibition leading to increased CaMKII catalytic activity, such as by Rem2 deletion, could lead to widespread changes in cellular structure and function. This is consistent with the many alterations we observe in our past and current studies of Rem2 deletion [51, 54, 55, 67, 7679]. Compellingly, the ability for Rem2 to inhibit CaMKII catalytic activity has already been linked to regulation of dendritic complexity [79].…”
Section: Discussionsupporting
confidence: 88%
“…While much experimentation remains to be done in order to explore a possible connection between synaptic and dendritic stability in the context of Rem2 function, some of our recent work may provide a hint. When Rem2 is deleted during the critical period, the same time period in which we observe dendritic instability here, changes in miniature excitatory post-synaptic current (mEPSC) frequency and amplitude were unchanged 4 days after Rem2 deletion, but by 10 days post-deletion a 25% decrease in mEPSC frequency was observed [76]. Here, we observed arbor changes as early as 5 days post-infection, suggesting that arbor changes may lead synaptic changes or occur simultaneously.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Rem2 is an experience-dependent negative regulator of segment number Rem2 function has previously been shown to be regulated by neuronal activity and sensory experience (Ghiretti et al, 2013Kenny et al, 2017;Moore et al, 2018). Therefore, we investigated whether visual experience was required for Rem2-dependent regulation of segment number.…”
Section: Rem2 Bidirectionally Regulates Segment Number In Distinct Dementioning
confidence: 99%
“…We previously showed that Rem2 is an activity-regulated gene as its mRNA expression is up-regulated by neuronal depolarization both in vitro and in vivo (13,14), and the Rem2 protein is also subject to activity-dependent post-translational modification (15). Moreover, we demonstrated using gene knockdown approaches in cultured rodent neurons and Xenopus laevis optic tectum that Rem2 regulates dendritic branching (13,16) in conjunction with CaMKII signaling.…”
mentioning
confidence: 99%